A spinster's guide to danger and dukes - Collins, Manda (Collins, Manda. Ladies most scandalous, 2023)
"Miss Poppy Delamare has been living a lie. To escape an odious betrothal, she hid as the quiet and unassuming Flora Deaver, secretary to London's most infamous female crime reporter. When her beloved younger sister is accused of murder, however, Poppy returns home to keep her sibling from the hangman's noose. But a collision with the most unexpected--and unwelcome--of travel companions interrupts her journey. To her surprise, the arrogant, albeit handsome, Duke of Langham offers to help clear her sister's name... in exchange for a favor of his own. Despite his rakish reputation, Joshua Fielding, the Duke of Langham, has no intention of abandoning a lady--or ladies--in need. A fake betrothal will benefit both him and Poppy. Langham will have protection from the society misses flocking to his grandmother's birthday celebration, and Poppy will have the power of the dukedom when proving her sister's innocence. Only the longer the ruse goes on, the less pretend the engagement feels, until neither are acting at all. But before Langham can propose in truth, their search reveals a tangled web of lies and betrayals leading back to his own family. With time running out to save Poppy's sister, can Poppy and Langham find the true murderer before the curtains fall?"--